Dalih Agama Untuk Kekerasan - Abu Yazid Adnan Quthny (Asy-Syari’ah : Jurnal Hukum Islam, 2015)
Politicization of religion is a phenomenon that often arises in a society, be it country macro community and society in general, both in structure and in the semi- structured and quasi-structure, and can even occur in the personal area, along with interest the culprit. This violence is not only done in one religion, but in a broader scale and the interests of a more global level, violence is also valid between one religion to another religion. Basically to realize the importance of politicians legitimized by coercing the political policy which lasted accompanying personal interest of the politicians. Thus, political factors into factors behind the violence in society. Violence in the name of religion has become a human tragedy that has long adorned the history of mankind. Normatively, no one of any religious teaching that encourages and recommends his followers to commit violence against followers of other religions outside the group. But historicallyfactual often encountered violence perpetrated by some members of the community in the name of religion.